2009
DOI: 10.3324/haematol.2009.010934
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell-derived microparticles induce plasmacytoid dendritic cell maturation: potential implications in inflammatory diseases

Abstract: BackgroundIncreased circulating endothelial microparticles, resulting from vascular endothelium dysfunction, and plasmacytoid dendritic cell activation are both encountered in common inflammatory disorders. The aim of our study was to determine whether interactions between endothelial microparticles and plasmacytoid dendritic cells could contribute to such pathologies. Design and MethodsMicroparticles generated from endothelial cell lines, platelets or activated T cells were incubated with human plasmacytoid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 49 publications
5
75
1
2
Order By: Relevance
“…In infectious conditions or in response to "danger" signals, pDC secrete IL-6 (7,8). In this paper, we reported increased IL-6 production by pDC in response to TGF-b, emphasizing the less recognized proinflammatory role of TGF-b (37).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In infectious conditions or in response to "danger" signals, pDC secrete IL-6 (7,8). In this paper, we reported increased IL-6 production by pDC in response to TGF-b, emphasizing the less recognized proinflammatory role of TGF-b (37).…”
Section: Discussionmentioning
confidence: 76%
“…Through IFN-a secretion, pDC can play a role in the antitumor effects induced by TLR7/9 ligand agonist (4-6) as well as in some autoimmune diseases (e.g., psoriasis and lupus) (3). However, pDC functions are not limited to IFN-a secretion because human and mouse pDC may secrete inflammatory cytokines such as IL-6 (7,8). Depending on the environmental signals, pDC have been described to initiate effective Th1 or Th2 cell responses (9).…”
mentioning
confidence: 99%
“…In mouse PDC, TAK-1/MAP3K7 activates the mitogen-activated protein kinase (MAPK) pathway that upregulates costimulatory molecule expression (e.g., CD40, CD80 or CD86) 36 . Both human and mouse PDC have been shown to secrete TNF-α 46, 45, 46 , IL-6 46, 45, 46 , IL-8 4547 or granulocyte macrophage colony-stimulating factor (GM-CSF) 45 . This TLR-induced cytokine synthesis is regulated in PDC by the translocation of NF-κB, p38 MAPK and c-Jun N-terminal kinase (JNK) into the nucleus.…”
Section: The Innate Immune Functions Of Plasmacytoid Dendritic Cellsmentioning
confidence: 99%
“…These NET contain DNA fibers, histones, as well as a large amount of LL37 and HMGB1 52, 53 . Human PDC can also be activated by CD154 from activated platelets 54 or endothelial-derived microvesicles 6, 46 . Other PRR are present in the cytoplasm of PDC and dedicated to RNA virus recognition.…”
Section: The Innate Immune Functions Of Plasmacytoid Dendritic Cellsmentioning
confidence: 99%
“…5 We then evaluated the role of LXR in PtdSerdependent MP internalization by PDC. After showing that MP uptake by PDC was PtdSer-dependent using AnxV, we observed that LXR stimulation significantly increased eFluor-labeled MP internalization by PDC ( Figure 1E).…”
mentioning
confidence: 99%